HUBUNGAN KEPEMIMPINAN DENGAN KINERJA KADER IMUNISASI DASAR CAMPAK PADA BAYI DI WILAYAH KERJA PUSKESMAS PADANG BULAN - Sri Yanti Purba; Rapael Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2019)
The posyandu cadre is a volunteer chosen from the community and to help develop community health by carrying out activities at the posyandu which include increasing immunization coverage. Cadre performance is the result / effort that has been done in the midst of the community. Based on the data obtained by researchers from the Padang Bulan Community Health Center the sample of this study were 75 cadres consisting of 6 Kelurahan namely: Kelurahan Petisah Hulu of 20 cadres, Kelurahan Darat by 5 cadres, Kelurahan Titi Rantai as many as 15 cadres, Padang Bulan Kelurahan as many as 10 cadres, Merdeka Village as many as 15 cadres, and Babura Village as many as 10 people. The purpose of this study was to look at the relationship between variables Openness, Empathy, Supporting Attitudes, and Measles Cadre Immunization Performance in infants. The research used is analytic descriptive and uses cross sectional design. Data were analyzed using Chi Square Test (CI = 95%, Î± 0.05). The results of data analysis showed that there was a relationship between Openness and Cadre Performance (p value = 0,000> 0.05), there was a relationship between Empathy and Cadre Performance (p value = 0,000> 0.05), and there was a relationship between variables Supporting Attitudes with Cadre Performance (p value = 0,000> 0.05). Therefore, it is expected that respondents will further enhance their understanding of what respondents should do in the field before the posyandu is conducted and after the posyandu is done in the field so as to improve the performance of the posyandu cadres.